Rapid degradation of malachite green by CoFe2O4–SiC foam under microwave radiation. Issue 6 (27th June 2018) - Mao, Yanpeng; Yang, Shanxiu; Xue, Chao; Zhang, Miaomiao; Wang, Wenlong; Song, Zhanlong; Zhao, Xiqiang; Sun, Jing
Abstract : This study demonstrated rapid degradation of malachite green (MG) by a microwave (MW)-induced enhanced catalytic process with CoFe2 O4 –SiC foam. The catalyst was synthesized from CoFe2 O4 particles and SiC foam by the hydrothermal method. X-ray diffraction and scanning electron microscopy techniques were used to confirm that CoFe2 O4 particles were settled on the surface of SiC foam. In this experiment, a novel fixed-bed reactor was set up with this catalyst for a continuous flow process in a MW oven. The different parameters that affect the MW-induced degradation rate of MG were explored. The MW irradiation leads to the effective catalytic degradation of MG, achieving 95.01% degradation within 5 min at pH 8.5. At the same time, the good stability and applicability of CoFe2 O4 –SiC foam for the degradation process were also discussed, as well as the underlying mechanism. In brief, these findings make the CoFe2 O4 –SiC foam an excellent catalyst that could be used in practical rapid degradation of MG.